Does Loosening the Inclusion Criteria of the CROSS Trial Impact Outcomes in the Curative-Intent Trimodality Treatment of Oesophageal and Gastroesophageal Cancer Patients?. Issue 9 (September 2022) - Abraham, A.G.; Joseph, K.; Spratlin, J.L.; Zebak, S.; Alba, V.; Iafolla, M.; Ghosh, S.; Abdelaziz, Z.; Lui, A.; Paulson, K.; Bedard, E.; Chua, N.; et al.
Abstract: Aim: To determine the efficacy of preoperative chemoradiotherapy as per the CROSS protocol for oesophageal/gastroesophageal junction cancer (OEGEJC), when expanded to patients outside of the inclusion/exclusion criteria defined in the original clinical trial. Materials and methods: Data were collected retrospectively on 229 OEGEJC patients referred for curative-intent preoperative chemoradiotherapy. Outcomes including pathological complete response (pCR), overall survival (OS), cancer-specific survival and recurrence-free survival (RFS) of patients who met CROSS inclusion criteria (MIC) versus those who failed to meet criteria (FMIC) were determined. Results: In total, 42.8% of patients MIC, whereas 57.2% FMIC; 16.6% of patients did not complete definitive surgery. The MIC cohort had higher rates of pCR, when compared with the FMIC cohort (33.3% versus 20.6%, P = 0.039). The MIC cohort had a better RFS, cancer-specific survival and OS compared with the FMIC cohort ( P = 0.006, P = 0.004 and P = 0.009, respectively). Age >75 years and pretreatment weight loss >10% were not associated with a poorer RFS ( P = 0.541 and 0.458, respectively). Compared with stage I–III patients, stage IVa was associated with a poorer RFS (hazard ratio (HR) = 2.158; 95% confidence interval (CI) = 1.339–3.480, P = 0.001). Tumours >8 cm in length or >5 cm in width had a trend towards worse RFS (HR = 2.060; 95% CI = 0.993–4.274, P = 0.052). Conclusion: Our study showed that the robust requirements of the CROSS trial may limit treatment for patients with potentially curable OEGEJC and can be adapted to include patients with a good performance status who are older than 75 years or have >10% pretreatment weight loss. However, the inclusion of patients with celiac nodal metastases or tumours >8 cm in length or >5 cm in width may be associated with poor outcomes. Highlights: CROSS protocol is a standard of care for oesophageal/gastroesophageal junction cancer. Expanding the inclusion criteria as per the CROSS protocol maybe beneficial. Patients with a good performance status who are older than 75 years may be included. Patients with >10% weight loss but with a good performance status may also benefit. GEJ cancers with celiac nodal metastases or large tumours have questionable benefit.